Drug Delivery Systems Based on Polysaccharides (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
We live in a constantly changing society, in which life expectancy has continuously increased, and, therefore, important health issues need to be solved. The development of nanotechnology with applications in the medical field—nanomedicine—has been proven to have strong therapeutic potential, especially by combining drugs with natural polymers, polysaccharides being most commonly used in the development of sustained and controlled release systems of biologically active principles. Polymeric nanoparticles loaded with drugs can actively target various diseases, being able to penetrate cells more effectively or succeed in overcoming some physiological barriers such as the blood–brain barrier. Drug-loaded hydrogels are used to treat dermal and dental conditions, and can act as scaffolds for the development of cell cultures with applications in tissue engineering. The recent literature abounds with articles discussing aspects of obtaining new polymer drug systems and their use in various biomedical applications. The editors of this Special Issue of the journal Molecules, entitled Drug Delivery Systems Based on Polysaccharides, are researchers with decades of experience in this field, and they consider justified and useful these several articles which report recent results of drug delivery systems based on polysaccharides and derivatives, respectively, and their biomedical applications. The authors of the articles are experts in the field, and the editors express their gratitude for the kindness and promptness with which they responded to the call to contribute the recently obtained results of their research to this specific edition of the journal Molecules.